BANTEN’S INDIGENOUS VISUAL STYLE IN THE ILLUSTRATIONS OF SAJARAH BANTEN MANUSCRIPT - Savitri Putri Ramadina; Yasraf Amir Piliang; Nuning Yanti Damayanti (Proceeding of International Conference on Art, Language, and Culture, 2019)
Sajarah Banten is a manuscript presumed to be made in 18th century and associated with the Sultanate of Banten. The Islamic influence was prevalent in the sultanate, such as the way the manuscript was written in Javanese-Arabic letters. This paper aims to research whether there were traces of indigenous Banten or Baduy people’s worldview and culture in the visual style of Sajarah Banten’s illustrations along with the Islamic influence. The research is conducted by applying art critic method to analyse and evaluate the visual style. Result shows that the illustrations contain both Islamic and indigenous Banten visual styles through the application of aniconism principle.